Centromeric localization and adaptive evolution of an arabidopsis histone H3 variant - Talbert, Paul B. (2002)
Centromeric H3-like histones, which replace histone H3 in the centromeric chromatin of animals and fungi, have not been reported in plants. We identified a histone H3 variant from Arabidopsis thaliana that encodes a centromere-identifying protein designated HTR12. By immunological detection, HTR12 localized at centromeres in both mitotic and meiotic cells. HTR12 signal revealed tissue- and stage-specific differences in centromere morphology, including a distended bead-like structure in interphase root tip cells. The anti-HTR12 antibody also detected spherical organelles in meiotic cells. Although the antibody does not label centromeres in the closely related species Arabidopsis arenosa, HTR12 signal was found on all centromeres in allopolyploids of these two species. Comparison of the HTR12 genes of A. thaliana and A. arenosa revealed striking adaptive evolution in the N-terminal tail of the protein, similar to the pattern seen in its counterpart in Drosophila. This finding suggests that the same evolutionary forces shape centromeric chromatin in both animals and plants.